The powers of music: Aesthetic theory and the invention of opera - Katz, Ruth (New Brunswick Transaction Publishers, 1994)
In this cultural history, Ruth Katz conceives of opera as a laboratory dedicated to exploration of the powers hidden in the interaction between words and music. Opera combines not only music and libretto, but the sensuality, acting out, and lyricism that characterize the popular culture of the Italians. The Powers of Music is thus a contribution to cultural studies, providing unique insight into the social meaning of opera in Italy.According to Katz, opera's origins in Renaissance Italy can be traced to numerous characteristics of life at that time. Among them are: the belief of the Humanists that the magical properties of music could be harnessed; the transition from polyphony to monody that gave musical expression to individualism; the melodramatic propensity of Italian culture reflected in its literary and theatrical arts; and the salons of Florentine aristocrats, scientists, and artists whose agenda included the challenge to rediscover how the ancient Greeks succeeded in heightening the rhetorical power of words by allying them with music. Katz discusses each of these factors in detail.In her new introduction, Katz reconsiders her original work by discussing three topics. The first has to do with the perception that there has been a major change in the academic climate for this kind of analysis. The second relates to her concern with the eighteenth-century expansion of the Florentine comparison of the attributes of the arts, from which music emerges as the purest of all, for being freest of external reference. Third, she reconsiders her initial impression that opera was on the wane. The Powers of Music is an intriguing study that will be of interest to sociologists, cultural historians, and scholars of communication and popular culture.